Thermo-moldable self-healing commodity plastics with heat resisting and oxygen-insensitive healant capable of room temperature redox cationic polymerization. Issue 5 (18th December 2014) - Zhu, Dong Yu; Guo, Jian Wei; Cao, Guang Sheng; Qiu, Wen Lian; Rong, Min Zhi; Zhang, Ming Qiu
Abstract : By using a novel healing chemistry of redox cationic polymerization, polystyrene with IBH/GMA capsules and NaBH4 particles molded via hot compression is proved to be self-healable at room temperature in air. Abstract : Commercially available polystyrene is coupled with self-healability by exploiting a novel healing chemistry of redox cationic polymerization. In this system, iodonium bis(4-methylphenyl) hexafluorophosphate (IBH)/glycidyl methacrylate (GMA) loaded microcapsules and NaBH4 particles are embedded in the matrix through compression molding. The healant is oxygen insensitive and heat resistant so that it meets the requirement of remendable thermoplastics.